Fe Vacancies Induced Surface FeO6 in Nanoarchitectures of N‐Doped Graphene Protected β‐FeOOH: Effective Active Sites for pH‐Universal Electrocatalytic Oxygen Reduction. (25th June 2018) - Li, Yan; Huang, Junheng; Hu, Xiang; Bi, Linlin; Cai, Pingwei; Jia, Jingchun; Chai, Guoliang; Wei, Shiqiang; Dai, Liming; Wen, Zhenhai
Abstract: Developing high‐active, good‐stable, and cost‐effective electrocatalyst for oxygen reduction reaction (ORR) in all‐pH medium is highly desired for the application of various fuel cell systems. Here, a network architecture hybrid with porous nitrogen‐doped graphene encapsulated β‐FeOOH nanoparticals (β‐FeOOH/PNGNs) as ORR electrocatalyst, which exhibits remarkable enhancement ORR performance in terms of activity and stability in pH‐universal medium is reported. Systematic characterization combining with X‐ray absorption fine structure analysis and the first principles simulations reveal that the as‐formed surface FeO6 active sites that induced by a mass of Fe vacancies in β‐FeOOH/PNGNs can significantly lower the thermodynamic barrier of the total reaction, and hence contribute to a remarkable enhancement in ORR activity. Abstract : The formation of the surface FeO6 active sites that induced by a mass of Fe vacancies in β‐FeOOH/porous nitrogen‐doped graphene encapsulated β‐FeOOH nanoparticles makes a remarkable enhancement in oxygen reduction reaction activity in all‐pH medium.